Recommendations for private security agent capacity building in Peru. Policy paper - Barnaby, Bruce (2022)
This paper is part of the study carried out by the Institute of Democracy and Human Rights of the Pontifical Catholic University of Peru (IDEHPUCP), with the support of Voluntary Principles on Security and Human Rights (VPI), between end of 2020 and beginning of 2022. Its objective was to explore and analyze human rights training in the private security sector in Peru. Thus, recommendations presented here are a continuation of the previous diagnosis document. Therefrom, some lines or content proposals are established that should be considered to strengthen the public policy of training in human rights, whose impact is not only limited to the actors directly involved in the sector, but also involves all users and civil society that interact with it on a daily basis.